Atmospheric research for adaptive optics - Bolbasova, Lidia A. (Atmospheric and oceanic optics)
Adaptive optics (AO) systems are an essential part of large astronomical telescopes and laser complexes operating through the atmosphere. Each AO system is individually designed; the requirements for the components and the performance of an AO system are determined by the intensity and distribution of turbulent fluctuations of the air refractive index over the radiation propagation path. In this work, we review the techniques and instruments for measuring and forecasting atmospheric conditions for AO, including devices and techniques developed at the Institute of Atmospheric Optics, Siberian Branch, Russian Academy of Sciences. The basic principles of atmospheric AO and the related atmospheric parameters are briefly described. Particular attention is paid to the parameter used for the estimation of capabilities of AO systems, i.e., the wind speed at a level of 200 hPa. The comparison with the data from foreign astronomical observatories is carried out. The necessity for atmospheric research for large Russian astronomical observatories is discussed.